Partner-based adherence intervention for second-line antiretroviral therapy (ACTG A5234): a multinational randomised trial. Issue 1 (January 2015) - Gross, Robert; Zheng, Lu; Rosa, Alberto La; Sun, Xin; Rosenkranz, Susan L; Cardoso, Sandra Wagner; Ssali, Francis; Camp, Rob; Godfrey, Catherine; Cohn, Susan E; Robbins, Gregory K; Chisada, Anthony; et al.
Summary: Background: Adherence is key to the success of antiretroviral therapy. Enhanced partner support might benefit patients with previous treatment failure. We aimed to assess whether an enhanced partner-based support intervention with modified directly observed therapy would improve outcomes with second-line therapy in HIV-infected patients for whom first-line therapy had failed. Methods: We did a multicentre, international, randomised clinical trial at nine sites in Botswana, Brazil, Haiti, Peru, South Africa, Uganda, Zambia, and Zimbabwe. Participants aged 18 years or older for whom first-line therapy had failed, with HIV RNA concentrations greater than 1000 copies per mL and with a willing partner, were randomly assigned (1:1), via computer-generated randomisation, to receive partner-based modified directly observed therapy or standard of care. Randomisation was stratified by screening HIV RNA concentration (≤10 000 copies per mL vs >10 000 copies per mL). Participants and site investigators were not masked to group assignment. Primary outcome was confirmed virological failure (viral load >400 copies per mL) by week 48. Analysis was by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT00608569 . Findings: Between April 23, 2009, and Sept 29, 2011, we randomly assigned 259 participants to the modified directly observed therapy group (n=129) or the standard-of-care group (n=130). 34 (26%) participants in the modified directly observed therapy group achieved the primary endpoint of virological failure by week 48 compared with 23 (18%) participants in the standard-of-care group. The Kaplan-Meier estimated cumulative probability of virological failure by week 48 was 25·1% (95% CI 17·7–32·4) in the modified directly observed therapy group and 17·3% (10·8–23·7) in the standard-of-care group, for a weighted difference in standard of care versus modified directly observed therapy of −6·6% (95% CI −16·5% to 3·2%; p=0·19). 36 (14%) participants reported at least one grade 3 or higher adverse event or laboratory abnormality (n=21 in the modified directly observed therapy group and n=15 in the standard-of-care group). Interpretation: Partner-based training with modified directly observed therapy had no effect on virological suppression. The intervention does not therefore seem to be a promising strategy to increase adherence. Intensive follow-up with clinic staff might be a viable approach in this setting. Funding: AIDS Clinical Trials Group and the National Institute of Allergy and Infectious Diseases, US National Institutes of Health.